2013
DOI: 10.1002/anie.201208550
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Domain Swaps Provide Insights into the Rules of Fungal Polyketide Synthase Programming and the Rational Synthesis of Non‐Native Aromatic Products

Abstract: Playing by the rules: Combinatorial domain swaps among “deconstructed” non‐reducing polyketide synthases (NR‐PKSs) revealed the rules behind product assembly (see scheme). The control exerted by individual catalytic domains was found to be sufficiently great that heterocombinations of domains from different NR‐PKSs synthesized products in a predictable manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 19 publications
(33 reference statements)
1
48
0
Order By: Relevance
“…From a matrix of six NR-PKSs enzyme components we have found that ACPs are substantially interchangeable; maintaining SAT–KS pairs is beneficial to overall synthetic efficiency; chain length is largely, but not exclusively, determined by the KS with occasional participation by the PT; PT active sites are unexpectedly accommodating with respect to the chain lengths of the polyketide intermediates presented to them, yet the regiochemistry of their cyclizations is tightly controlled; and, as noted above, the TE is crucial to success. Enzyme-directed cyclizations must outpace spontaneous reaction and TE-mediated editing, 52, 53 but “rules” have emerged from these studies where rapid combinatorial experiments can be used to quickly survey potential heterodomain combinations for assembly into single PKS chimeras for more efficient synthesis. 53 …”
Section: Behaviour and Engineering Of Nr-pkssmentioning
confidence: 99%
“…From a matrix of six NR-PKSs enzyme components we have found that ACPs are substantially interchangeable; maintaining SAT–KS pairs is beneficial to overall synthetic efficiency; chain length is largely, but not exclusively, determined by the KS with occasional participation by the PT; PT active sites are unexpectedly accommodating with respect to the chain lengths of the polyketide intermediates presented to them, yet the regiochemistry of their cyclizations is tightly controlled; and, as noted above, the TE is crucial to success. Enzyme-directed cyclizations must outpace spontaneous reaction and TE-mediated editing, 52, 53 but “rules” have emerged from these studies where rapid combinatorial experiments can be used to quickly survey potential heterodomain combinations for assembly into single PKS chimeras for more efficient synthesis. 53 …”
Section: Behaviour and Engineering Of Nr-pkssmentioning
confidence: 99%
“…The C -terminal His 6 -tagged PksA SAT–KS–MAT tridomain and PT–ACP didomain were over-produced in E. coli and purified by Co 2+ -affinity chromatography as previously described(18). Potential starter units were presented as N -acetylcysteamine (SNAC) thioesters (Figure 1), which were prepared by coupling of N -acetylcysteamine to commercially-available or readily synthesized carboxylic acids (see Supplemental Information).…”
Section: Resultsmentioning
confidence: 99%
“…Reactions of 6 , 8 and 9 were less efficient in naphthopyrone product formation and correspondingly gave increased shunt and truncation products appearing at early retention times in the HPLC chromatogram (Figures S2, S4, S5). Recent deconstruction and domain “swapping” or heterodomain combinatorial experiments have revealed tight control of overall polyketide chain length to largely ± one ketide (C 2 ) extension, while the PT domain exerts strict programming of ring formation despite receiving chain lengths both shorter and longer than wild-type(18, 19). Reactions utilizing the C 8 starter unit 9 exemplify this tight chain length control, as one fewer ketide extension was performed to give a naphthopyrone product with the native C 20 chain length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibilities can be envisioned where their intrinsic substrate flexibility can be exploited. What is lost in binding affinity may well be compensated for by high effective concentration provided by carrier-protein mediated intraprotein transfer [18].…”
Section: Discussionmentioning
confidence: 99%